UPAYA PENINGKATAN MOTIVASI PEMBELAJARAN LARI JARAK PENDEK DENGAN PEMBERIAN METODE BERMAIN PADA SISWA SMP - Bino, Nikodimus; Haetami, Mimi; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakThe method used is anThe problem in this research is whether the method of play can increaces the motivation of learning run short distance lerners class C seven junior high school Santo Gabriel Sekadau Regency. The purpose of this research was conducted to find out the improvement of learning motivation run short distance by administering method play on learners class C seven junior high school, Santo Gabriel Sekadau Regency.The methods used to research a class act with a sampling, the entire grade seven C as 39 students.As for the result obtained from this research is the resultof learning one cycle average 62,392%, cycle two average 70,94%, whereas the Cycle of three 76,35%. Means the results of the study ran the short distance with the method improvement effectiveness.Â Keywords:The activity of the teacher, the learner activity, and method of approach to the game.Â